2021
DOI: 10.1002/cssc.202100332
|View full text |Cite
|
Sign up to set email alerts
|

Perovskites on Ice: An Additive‐Free Approach to Increase the Shelf‐Life of Triple‐Cation Perovskite Precursor Solutions

Abstract: The development of stable perovskite precursor solutions is critical if solution‐processable perovskite solar cells (PSCs) are to be practically manufacturable. Ideally, such precursors should combine high solution stability without using chemical additives that might compromise PSC performance. Here, it was shown that the shelf‐life of high‐performing perovskite precursors could be greatly improved by storing solutions at low‐temperature without the need to alter chemical composition. Devices fabricated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…There are many differences between these two systems that could result in these different aging processes (this includes solvent blend, molarity and solids composition). Based on what we have found previously, 43 we speculate that deprotonated methylammonium (MA + ) is very unstable in TC solutions. We hereby note that additional molecules in the TC sample (formamidinium, bromine, cesium) could potentially have a stabilizing effect on some of the intermediate complexes formed.…”
Section: Resultssupporting
confidence: 52%
“…There are many differences between these two systems that could result in these different aging processes (this includes solvent blend, molarity and solids composition). Based on what we have found previously, 43 we speculate that deprotonated methylammonium (MA + ) is very unstable in TC solutions. We hereby note that additional molecules in the TC sample (formamidinium, bromine, cesium) could potentially have a stabilizing effect on some of the intermediate complexes formed.…”
Section: Resultssupporting
confidence: 52%
“…We have previously demonstrated that storing precursor inks at low‐temperature can extend their shelf life, however solvent choice is known to have a significant impact on solution stability. [ 69 ] We therefore investigated the shelf‐life of the 1:9 THF:2‐ME MAPbI 3 precursor ink when stored at low temperature (≈4 °C). To do this, devices were periodically fabricated from a single batch of a fridge‐stored ink.…”
Section: Resultsmentioning
confidence: 99%
“…It is notable that the doublet peaks at δ 2.512 ppm and δ 2.522 ppm are only observed in the aged precursor solution (80 h) without appearing in the fresh precursor solution, 34 which implies that the dimethylammonium (DMA) is slowly formed during the aging process. The formation mechanisms of MFA, DMFA, and DMA in the perovskite precursor solution are accordingly addressed in Scheme 1, where iodide, MA and/or formamidinium (FA) eventually act as reactants to produce either MFA, DMFA, or DMA 35–37 …”
Section: Resultsmentioning
confidence: 99%
“…The formation mechanisms of MFA, DMFA, and DMA in the perovskite precursor solution are accordingly addressed in Scheme 1, where iodide, MA and/or formamidinium (FA) eventually act as reactants to produce either MFA, DMFA, or DMA. [35][36][37] FTIR spectra were measured to understand the aging effect in the precursor solution. In Figure 2a the observed peaks at 1542.022 cm À1 and 1711.751 cm À1 correspond to COO À antisymmetric stretch (COO À as ) and C O stretch vibration, respectively, [38][39][40][41] being ascribed to the carboxylate of propionate in MAP.…”
Section: Resultsmentioning
confidence: 99%